Fulfilment of Early Childhood Rights for Children of Inmates Who Live in Prisons: A Case Study of Semarang Women's Prison - Elisa Rahmawati; Diana Diana (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to determine the prison's efforts in fulfilling the rights of children of correctional prisoners (WBP) both those who are still in the womb and those under 3 years old. In addition, this study aims to ensure the psychological stability of WBP who are mothers as the main caregivers of children. The research was conducted with a case study qualitative research design. Primary data sources were obtained from information from interviews with prison staff and prisoners who have experienced pregnancy and parenting in prison. While secondary data sources were taken from documentation of previous sources including child development records and Instagram media content studies. Data collection was conducted through interviews, observation, and documentation. The data were analyzed using thematic qualitative data analysis techniques. The results of the study found that prisons provide easy access to health, the provision of health and development facilities, and a guarantee of security from violence and discrimination for early childhood. While the second finding is that the mother's psychological condition is still stable so that there is minimal parenting stress that leads to violence. This is due to the support of psychological services for prisoners and the positive relationship between the prison and the mother (WBP). Implications for further research are written in this article.